ANALISIS PERENCANAAN PERAWATAN MESIN STERILIZER DENGAN METODE OVERALL EQUIPMENT EFFECTIVENESS DAN SIX BIG LOSSES DI PT TORGANDA PKS RANTAU KASAI - Rini Halila Nasution; Yetti Meuthia Hasibuan; Uun Novalia Harahap; Sekar Ayu Ony Ningrum; Alda Febriansyah Chaniago (Universitas Harapan Medan, 2020)
PT. Torganda PKS Rantau Kasai is one of the palm oil processing plants that produce crude palm oil (CPO), and palm kernel (kernel) products. As the production process progresses, there is a problem with the sterilizer, namely downtime. The purpose of this study is to calculate the effectiveness of the sterilizer machine and provide a proposal for machine maintenance planning. The methods used are the Overall Equipment Effectiveness (OEE) and Six Big Losses methods to calculate the effectiveness of the machine and find out what losses are the largest. The results of the calculation of the effective value of the sterilizer machine from May 2021 to April 2022 the average availability ratio value is 96.33%, the performance efficiency of 64.40%, and the rate of the quality product is 100%. o the value of Overall. Equipment Effectiveness (OEE) is 62.04%. This value is still below the predetermined World OEE standard of 85%. The value of six big losses that had the biggest effect on the decline in the effectiveness of sterilizers was reduced speed losses, which was 82.46%. The proposed maintenance planning carried out is to improve the maintenance of the sterilizer machine on a daily, weekly, and monthly basis, apply preventive and corrective maintenance on the sterilizer machine, and conduct periodic inspections on the sterilizer machine.